How does transitional justice matter? Expanding and refining quantitative research on the effects of transitional justice policies. Issue 4 (8th August 2022) - Murphy, Matt
Abstract: Although the field of transitional justice is expanding rapidly, research on its effects remains underdeveloped, despite its presumed importance for human rights and democratic consolidation. The field suffers from incompatible approaches and definitions, disputed causal models and conclusions, and a multiplicity of dependent variables. Quantitative work struggles to ground measurement and hypothesis testing in nuanced conceptions of transitional justice's causal processes. Robust understanding of effects requires integrating qualitative and quantitative approaches while balancing accuracy with parsimony. This article first revisits and builds on a key quantitative work: Olsen et al.'s Transitional justice in balance (2010 ). Using an expanded dataset to repeat their descriptive and statistical analysis of the effects of transitional justice, the article finds results only marginally consistent with their original findings. This reassessment is the basis for proposed revisions to their causal model, conceptualization, measurement, and hypothesis testing. The proposed approach includes a two-step causal model, differentiated measurement of transitional justice mechanisms, and hypotheses that are more deeply grounded in the insights of qualitative studies. These revisions provide a framework with rich potential for comparative quantitative analysis of the effects of transitional justice.